A direct numerical simulation analysis of pressure variation in turbulent premixed Bunsen burner flames-Part 1: Scalar gradient and strain rate statistics. (15th September 2018) - Klein, M.; Alwazzan, D.; Chakraborty, N.
Highlights: Parametric analysis of high pressure Bunsen burner flames using DNS. Mean values of scalar gradient and strain rate are unaffected by pressure change. High pressure flames are likely to exhibit the Darrieus–Landau (DL) instability. The DL instability affects dilatation rate and tangential strain rate statistics. Modelling implications for elevated pressure flames have been discussed. Abstract: Three-dimensional simple chemistry Direct numerical simulations (DNS) of Bunsen burner flames have been carried out for different pressure values. A number of cases have been considered for the same set of values of mean and root-mean-square inlet velocities normalised by the laminar burning velocity and the integral length scale normalised by the nozzle diameter. The modifications of laminar burning velocity and flame thickness with pressure lead to an increase in both flow and turbulent Reynolds numbers with increasing pressure. This also gives rise to changes in Damköhler number and Karlovitz numbers for these flames and thus they occupy different locations on the regime diagram. For this reason, two additional cases at the lowest pressure have been simulated to match the turbulent Reynolds number of the highest-pressure case by changing the normalised root-mean-square velocity in one case, whereas the integral length scale is modified in the other case. It has been found that pressure and turbulent Reynolds number variations do not have significant influences on the mean behaviours of the magnitude of the reaction progress gradient (i.e. Surface Density Function) and fluid-dynamic normal strain rate. However, the length scale separation between the nozzle diameter and flame thickness increases with increasing pressure, which makes the occurrence of the Darrieus–Landau (DL) instability highly likely for the flames at elevated pressures. The presence of the DL instability affects the flame curvature statistics, which in turn influence the mean behaviours of the dilatation rate and fluid-dynamic tangential strain rate.